Juridical review of companies and limited liability companies - Henny Yunita Puranto (Jurnal Cakrawala Hukum, 2022)
Limited Liability Companies are formed by at least 2 (two) founders, and their formation is based on an agreement. At the end of 2020, the government issued a law known as the Job Creation Law (after this, referred to as UUCK). UUCK was established to promote economic development and support the business environment in Indonesia. UUCK has a new form of business, individual ownership, by the nature of micro and small businesses. Sole proprietorships were established under the revised UUCK section of the Limited Liability Company Law Number 40 of 2007 (after this referred to as the UUPT), and the revised UUPT contains several provisions that can cause conflicts in the future, one of which is a merger. Greetings. However, regarding establishing an individual business entity that one person can incorporate, this provision does not fulfill the parts of the agreement mentioned in the sense of a corporation. One of the contract conditions is that it must be carried out by at least 2 (two) people. A single company with a new concept requires further research.How to cite item: Puranto, H. Y., (2022), Juridical review of companies and limited liability companies. Jurnal Cakrawala Hukum, 13(3)262-271. doi:10.26905/idjch.v13i3.6086.